NPC1 Deficiency Contributes to Autophagy-Dependent Ferritinophagy in HEI-OC1 Auditory Cells - Liang, Lihong; Wang, Hongshun; Yao, Jun; Wei, Qinjun; Lu, Yajie; Wang, Tianming; Cao, Xin (Frontiers in Molecular Biosciences, 2022)
Niemann-pick Type C disease (NPCD) is a rare genetic syndrome characterized by cholesterol accumulation in multiple organelles, in which the gene deficiency of NPC intracellular cholesterol transporter 1 (NPC1) mainly accounts for. It is reported that part of the NPCD patients exhibiting clinical feathers of progressive hearing loss at high frequency and iron disorder, but the underlying relationship is unknown. A recent study has reported that ferroptosis contributes to the impairment of cochlear hair cells that related to hearing sensory. In this study, we generated Npc1-deficient HEI-OC1 cells to show the effect of NPC1 deficiency on cochlear outer hair cells. We found that Npc1 deficiency enhances autophagy-dependent ferritinophagy to release Fe (II). Our work provides important insights into the effect of Npc1 deficiency in auditory cells, indicating that it induces ferroptosis and results in hearing loss.